Alzheimer's disease and gastrointestinal microbiota; impact of Helicobacter pylori infection involvement. (4th March 2021) - Doulberis, Michael; Kotronis, Georgios; Gialamprinou, Dimitra; Polyzos, Stergios A.; Papaefthymiou, Apostolis; Katsinelos, Panagiotis; Kountouras, Jannis
Abstract: Background: Alzheimer disease (AD) is a leading cause of global burden with great impact on societies. Although research is working intensively on promising therapy, the problem remains up-to-date. Among the various proposed hypotheses regarding causality and therapy, emerging evidence supports the hypothesis that gastrointestinal microbiota through the so-called 'gut-brain axis' interacts with immune system and brain and shape the balance between homeostasis and disease; the involvement of gastrointestinal microbiota in the pathophysiology of AD is less defined, even though the role of 'gut-brain axis' has been well verified for other neurodegenerative conditions. Methods: We performed a systematic review of PubMed/MEDLINE database from 1 st January 1990 to 17 th October 2018, to investigate the accessible literature regarding possible association between AD and gastrointestinal microbiota. Inclusion criteria were available full text in English language, original clinical papers implicating AD patients and any sort of gastrointestinal microbiota. Results: Through our query, an initial number of 241 papers has been identified. After removing duplicates and through an additional manual search, twenty-four papers met our inclusion criteria. The great majority of eligible publications supported a possible connection between AD and gastrointestinal microbiota. The most common investigated microorganism was Helicobacter pylori. Conclusion: Our own systematic review, showed a possible association between AD and gastrointestinal microbiota mainly including Helicobacter pylori, and thus further research is required for substantiation of causality as well as for the establishment of promising novel therapies.